Criminal Responsibility for Perpetrators Distributing Content Electronic Gambling (Analysis of Decision Number: 367/ Pid.Sus /2025/Pn. Mdn) - Riswan Munthe (Faculty of Law, Universitas Pekalongan, 2025)
Study This to describe related problem gambling that focuses on regulation offense load gambling based on regulation legislation in Indonesia and Accountability criminal for perpetrator distribute gambling through Electronic analysis decision number : 367/ Pid.Sus /2025/ PN . Mdn ). The research method used namely type study legal normative , so the data used is secondary data , and do data analysis with qualitative . Based on results found that arrangement offense load gambling based on regulation legislation in Indonesia , namely load gambling has regulated in the Criminal Code and Law Law No. 7 of 1974 concerning Orderliness Gambling , if offense gambling normal . As well as Article 27 paragraph (2) of the Law Republic of Indonesia Number 1 of 2024 Concerning Change Secondly , under the Law Republic of Indonesia Number 11 of 2008 Concerning Information and Transactions Electronics . Accountability criminal for perpetrator distribute gambling through Electronic based on analysis decision number : 367/ Pid.Sus /2025/PN. Mdn ) namely accountability criminal has fulfil elements , which are the perpetrators proven without right distribute , transmit and or make can accessible information electronics and or document electronics that have load gambling so that element the has fulfilled and has been dropped punishment criminal in accordance Article 27 paragraph (2) in conjunction with Article 45 paragraph (3) of the Law Republic of Indonesia Number 1 of 2024 Concerning Change Secondly , under the Law Republic of Indonesia Number 11 of 2008 Concerning Information and Transactions Electronic has fulfilled , and stated has proven in a way valid and convincing do act criminal gambling